Priming agents transiently reduce the clearance of cell-free DNA to improve liquid biopsies - Martin-Alonso, Carmen; Tabrizi, Shervin; Xiong, Kan; Blewett, Timothy; Sridhar, Sainetra; Crnjac, Andjela; Patel, Sahil; An, Zhenyi; Bekdemir, Ahmet; Shea, Douglas; Wang, Shih-Ting; Rodriguez-Aponte, Sergio A.; et al. (Science, 2024)
Liquid biopsies enable early detection and monitoring of diseases such as cancer, but their sensitivity remains limited by the scarcity of analytes such as cell-free DNA (cfDNA) in blood. Improvements to sensitivity have primarily relied on enhancing sequencing technology ex vivo. We sought to transiently augment the level of circulating tumor DNA (ctDNA) in a blood draw by attenuating its clearance in vivo. We report two intravenous priming agents given 1 to 2 hours before a blood draw to recover more ctDNA. Our priming agents consist of nanoparticles that act on the cells responsible for cfDNA clearance and DNA-binding antibodies that protect cfDNA. In tumor-bearing mice, they greatly increase the recovery of ctDNA and improve the sensitivity for detecting small tumors.